2022
DOI: 10.37898/spc.2022.7.2.161
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Health Realization/Innate Health Psycho-education For Individuals With Eating Disorders: Pilot Study

Abstract: Eating disorders are associated with high rates of mortality, disability, and poor motivation for change. Psychological therapies are the first line treatment, yet outcomes are poor, and drop- out rates high. Health Realization/Innate Health (HR/IH) psycho-education offers an alternative intervention which can be delivered in groups engaging participants’ innate capacity for well- being and resilience. Eight female participants with anorexia nervosa (mean age 27.75, SD 14.34) from the CONNECT Eating Disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Empirical evidence across innate health-focused interventions found positive changes in levels of (a) stress, depression, and anxiety as well as enhanced well-being among female Somali refugees in the midwestern region of the United States (Robertson et al, 2019); (b) drug use, well-being, and commitment to sobriety among residents at a Northeastern, U.S. treatment facility ; and, (c) in well-being, resilience, and impulse control among adolescents living in London, England (Kelley et al, 2021). While there are several small and promising studies (Catherine-Gray et al, 2022;El-Mokadem et al, 2023;Felix et al, 2022;Rees-Evans & Pevalin, 2017), the first large-scale randomized controlled trial of an innate health intervention demonstrated significant improvements in communication, decision-making, problem-solving, emotional regulation, and resilience in children (Green et al, 2021a(Green et al, , 2021b.…”
Section: Innate Healthmentioning
confidence: 99%
“…Empirical evidence across innate health-focused interventions found positive changes in levels of (a) stress, depression, and anxiety as well as enhanced well-being among female Somali refugees in the midwestern region of the United States (Robertson et al, 2019); (b) drug use, well-being, and commitment to sobriety among residents at a Northeastern, U.S. treatment facility ; and, (c) in well-being, resilience, and impulse control among adolescents living in London, England (Kelley et al, 2021). While there are several small and promising studies (Catherine-Gray et al, 2022;El-Mokadem et al, 2023;Felix et al, 2022;Rees-Evans & Pevalin, 2017), the first large-scale randomized controlled trial of an innate health intervention demonstrated significant improvements in communication, decision-making, problem-solving, emotional regulation, and resilience in children (Green et al, 2021a(Green et al, , 2021b.…”
Section: Innate Healthmentioning
confidence: 99%